Study of influencing factors in the process of biosorption in batches of Fe3+, Ni2+ and Cd2+ using bioadsorbent derived from Pachira aquatica Aubl. (Research, Society and Development, 2021)
Lignocellulosic materials have been studied as possible adsorbents applied in the treatment of effluents containing metallic ions. An example of a material is the Pachira aquatica’s peel, which has favorable characteristics for the biosorption process. The present study aimed to contribute to biosorption studies using the Pachira aquatic, investigating the influencing factors in the biosorption process of Fe3+, Ni2+ and Cd2+ through experimental planning. It was used the complete factorial design with three central points, using four factors with two levels each (upper and lower), totaling 19 experiments (24+3). The beginning of the experiments started with the preparation of the bioadsorbent material and metallic solutions, followed by their application in batch biosorption tests with variation of the factors temperature, pH, mass of bioadsorbent and concentration of adsorbate. At the end of the tests, satisfactory results were obtained for the removal of metallic ions, especially when the factors pH, mass of bioadsorbent and adsorbate concentration were at their highest levels. The temperature factor was not significant for Fe3+ and Cd2+ adsorption and little significant for Ni2+. Thus, the use of the lower temperature level (30 °C), because promote more economical processes. Using the factors in their optimal values (mb=0,5g e ca=70mg/L), there was removal of 100%, 99% and 100% of Fe3+, Ni2+ and Cd2+, respectively. It was concluded from the results obtained that charcoal produced from Pachira aquatica it is efficient for Fe3+, Ni2+ and Cd2+ biosorption.